2014
DOI: 10.5861/ijrse.2014.783
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the most Flow Inducing Genres

Abstract: The present study aims at examining the extent to which three discourse genres of descriptive, expository, and narrative would be flow inducing. In other words, it attempts to testify the role of the text in promoting optimal experience on the one hand, and to identify which discourse genre would be the most flow inducing, on the other hand. To this end, a community sample of 60 participants comprising of 16 males and 44 females from various English language institutes in Mashhad, volunteered to take part in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Moreover, the results confirmed findings of Mirlohi, Egbert and Ghonsooly (2011) in the field of translation along with Ghonsooly and Hamedi (2014) in the EFL context in that the descriptive mode revealed to be the most and the narrative as the least flow inducing genres. More importantly, the ultimate issue that may make a substantial contribution to the higher productivity of instructional materials is that the study corroborates McQuillan and Conde's (1996) assertion that the students' selected texts are far likelier to produce flow than the assigned texts.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Moreover, the results confirmed findings of Mirlohi, Egbert and Ghonsooly (2011) in the field of translation along with Ghonsooly and Hamedi (2014) in the EFL context in that the descriptive mode revealed to be the most and the narrative as the least flow inducing genres. More importantly, the ultimate issue that may make a substantial contribution to the higher productivity of instructional materials is that the study corroborates McQuillan and Conde's (1996) assertion that the students' selected texts are far likelier to produce flow than the assigned texts.…”
Section: Discussionsupporting
confidence: 77%
“…A few studies which have applied flow theory in language learning have confirmed the relationship between flow and classroom language learning (Egbert, 2003;Ghonsooly & Hamedi, 2014;McQuillan & Conde, 1996;Schmidt & Savage, 1992). As noted, among the classroom activities, reading is reported as a flow inducing task in that the recreation of the writer's intended meaning can be accomplished only when the reader integrates the textual information with his background knowledge (Haji Maibodi, 2008).…”
Section: Flow In Language Learning and Readingmentioning
confidence: 99%
See 3 more Smart Citations